2015
DOI: 10.1111/lre.12091
|View full text |Cite
|
Sign up to set email alerts
|

The responses of Nile tilapia Oreochromis niloticus (Linnaeus, 1758) in Lake Wamala (Uganda) to changing climatic conditions

Abstract: Changes in the catches of Nile tilapia, Oreochromis niloticus (Linnaeus, 1758), in Lake Wamala (Uganda) have been observed since its introduction. The factors contributing to these changes, however, are not well understood. This study examined changes in species composition, size structure, size at first maturity, length-weight relationship and condition factor of Nile tilapia in Lake Wamala, in relation to changes in temperature, rainfall and lake depth, to provide a better understanding of the possible role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…After correlation coefficient were less than 0.8 and log (a') vs b filtering, 28 were still below 2.5. We then reviewed the original literature and found that studies have shown that poor environmental conditions, lack of food, harsh climate and high population density can lead to low b-values (Vianny et al, 2015;Batool et al, 2017;Obayemi et al, 2019;Yem et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…After correlation coefficient were less than 0.8 and log (a') vs b filtering, 28 were still below 2.5. We then reviewed the original literature and found that studies have shown that poor environmental conditions, lack of food, harsh climate and high population density can lead to low b-values (Vianny et al, 2015;Batool et al, 2017;Obayemi et al, 2019;Yem et al, 2020).…”
Section: Resultsmentioning
confidence: 99%